Prevention of Wogonin on Colorectal Cancer Tumorigenesis by Regulating p53 Nuclear Translocation - Feng, Qian; Wang, Haojia; Pang, Jiaying; Ji, Liyan; Han, Jiada; Wang, Ying; Qi, Xiaoxiao; Liu, Zhongqiu; Lu, Linlin (Frontiers in Pharmacology, 2018)
The tumor suppressor protein p53 plays an important role in the development and progression of colon cancer, and the subcellular organelle localization directly affects its function. Wogonin (5,7-dihydroxy-8-methoxyflavone), a mono-flavonoid extracted from root of Scutellaria baicalensis Georgi, possesses acceptable toxicity and has been used in colorectal cancer chemoprevention in pre-clinical trials by oncologist. However, the underlying anti-colon cancer mechanisms of wogonin are not yet fully understood. In the present study, the effect of wogonin on the initiation and development of colitis-associated cancer through p53 nuclear translocation was explored. AOM-DSS colorectal cancer animal model and human colorectal cancer HCT-116 cell model were used to evaluate the in vivo and in vitro anti-lung cancer action of wogonin. We observed that wogonin showed a dramaticlly preventive effect on colon cancer. Our results showed that wogonin caused apoptotic cell death in human colorectal cancer HCT-116 cell through increased endoplasmic reticulum stress. Meanwhile, excessive endoplasmic reticulum stress facilitated the cytoplasmic localization of p53 through increasing phosphor-p53 at S315 and S376 sites, induced caspase-dependent apoptosis and inhibited autophagy. Furthermore, we verified the chemoprevention effect and toxicity of wogonin in vivo by utilizing an AOM-DSS colon cancer animal model. We found that wogonin not only reduced tumor multiplicity, preserved colon length to normal (6.79 ± 0.34 to 7.41 ± 0.56, P< 0.05) but also didn’t induce side effects on various organs. In conclusion, these results explain the anti-tumor effect of wogonin in colorectal cancer and suggest wogonin as a potential therapeutic candidate for the therapeutic strategy in colorectal cancer treatment.